ST segment elevation associated with hydrochloric acid ingestion: A case report. Issue 47 (November 2017) - Yeh, I-Jeng; Liu, Kuan-Ting
Abstract: Rationale: Electrocardiography (ECG) was used to diagnose acute coronary syndrome, but many other diseases may also result in ST segment change. We report one case of ingested hydrochloric acid present with ST segment elevation in the ECG. However, subsequent coronary angiography did not reveal significant coronary occlusion. Patient concerns: An 83-year-old female was transferred to our emergency department (ED) from the branch hospital due to ingestion of toilet bowl cleaner containing 9.5% hydrochloric acid. She complained about chest pain and 12-lead ECG showed ST segment elevation at lead II, III, and aVF. The blood examinations revealed elevation of aspartate transaminase (69 IU/L), thrombocytopenia (62, 000/μL), and acidosis (pH 7.311, pCO2 27 mm Hg, HCO3 13.3 mmol/L). Creatine kinase-MB and troponin I did not elevate then. Diagnoses: After transferred to our ED, coronary angiography was done within 1 hour. Angiography showed 60% stenosis in the segment 7 of left anterior descending coronary artery and 30% nonsignificant stenosis in the segment 2 of right coronary artery, with no apical ballooning. No significant lesion consistent with ST segment elevation myocardial infarction was found. Interventions: Conservative treatment was chosen. Outcomes: Bradycardia was followed by cardiac arrest that developed 4 hours later. Cardiopulmonary resuscitation was applied and the patient became shock status after return of spontaneous circulation. The patient was admitted to the intensive care unit and expired on next day. Lessons: Patients of ingested hydrochloric acid present with ST segment elevation in the ECG may not indicate coronary artery disease. This ECG finding may be a poor prognostic index in such patients.